DEVELOPMENT OF GEOGRAPHY LEARNING TOOLS BASED ON THE INDONESIAN NATIONAL QUALIFICATION FRAMEWORK (KKNI) CURRICULUM - Hidayaht, Achmad Nur; Budiaman, Budiaman; Kurniawan, Nandi (GeoEco, 2022)
The development of learning tools is one of the efforts to improve the quality of education as an effort to provide complete and systematic learning tools. One of them is the development of learning tools including (RPS) Semester Learning Plans and (RTM) Student Assignment Designs according to the KKNI in introductory geography courses. The development of learning tools in this study used the ADDIE (Analysis, Design, Development or Production, Implementation or Delivery, and Evaluations) model, with data collection instruments through questionnaires and validation sheets with descriptive analysis techniques. The results of the needs analysis showed that 74.4% needed an RPS adjustment and 78.9% needed the development of teaching materials in a social study program (PIPS), while the evaluation of the development validity (RPS) of Semester Learning obtained an average score of 3.59 while for the average instrument assessment (RTM) the Student Assignment Plan was obtained. the mean score is 3.75 with a mean value of 3.67 with valid criteria. These results indicate that the development of learning tools is following the KKNI and is ready to be implemented in learning activities.